The patient's journey with chronic hepatitis C from interferon plus ribavirin to interferon‐ and ribavirin‐free regimens: a study of health‐related quality of life. Issue 3 (9th June 2015) - Younossi, Z. M.; Stepanova, M.; Nader, F.; Lam, B.; Hunt, S.
Summary Background Interferon and ribavirin negatively impact health‐related quality of life (HRQL) during treatment. Aim To compare the impact of interferon and/or ribavirin‐containing regimens on HRQL to interferon‐ and ribavirin‐free regimens. Methods HRQL data from nine multinational phase 3 clinical trials of sofosbuvir (SOF)‐based regimens with and without ledipasvir (LDV), pegylated interferon (IFN) or ribavirin (RBV) were used. The Short Form‐36 (SF‐36) HRQL questionnaire was administered to subjects prospectively at baseline, during treatment, and 12 and 24 weeks after treatment cessation. Results A total of 3460 CH‐C with SF‐36 data were included (52.2 ± 10.3 years, 62.6% male, 73.6% treatment‐naïve, 15.0% cirrhotic, 68.2% HCV genotype 1 and 20.1% genotype 3). Compared to baseline HRQL, at the end of treatment, severe HRQL decrements were noted in IFN + RBV ± SOF regimens (on average, −3.8 to −24.3 on a 0–100 scale for different HRQL domains), while moderate decrements were noted in SOF + RBV ± LDV (−2.8 to −8.6). In contrast, in SOF/LDV without RBV, HRQL improvements were noted during treatment (+2.3 to +5.2). By 12 weeks post‐treatment, HRQL returned to baseline in IFN + RBV ± SOF (P > 0.05) and improved in all IFN‐free arms (+2.6 to +7.8). In multivariate analysis, a lower end of treatment HRQL was associated with IFN + RBV + SOF and a higher end of treatment HRQL was associated with SOF/LDV. By post‐treatment‐12, SOF/LDV was additionally associated with higher mental health scores. These improvements in HRQL scores were maintained 24 weeks post‐treatment. Conclusions Removing interferon and ribavirin has led to substantial improvement of health‐related quality of life during treatment. This may result in better patient experience and higher adherence to treatment regimen.